HISTORICAL DEVELOPMENT OF TOLL COLLECTION IN THE TERRITORY OF PRESENT-DAY SLOVAKIA (Perner's Contacts, 2010)
This article is oriented to area of historical development of toll collection in the territory of present-day Slovakia. The collection of market and especially road toll as means to road building and maintenance is presented in more detail. An actual situation of the new system of tolling a specified road infrastructure in the Slovak Republic is described in conclusion this paper.
Keywords: market and road tool; toll-house; road maintenance; highway; 1st class road